PENGARUH GLOBALISASI TERHADAP POLITIK NEGARA - Muhammad Nursyawal; Kustiawan, Kustiawan; 20, Aisyah; Nur Maria Magdalena; Steviana Br Sihombing (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
Globalization is an all-encompassing process in various fields of life so that there are no longer any real boundaries that bind countries, making it difficult to filter or control. Globalization is physically marked by the development of cities that are part of the world city network. This can be seen from telecommunications infrastructure, transportation networks, international companies and their branches. The purpose of this research is to analyze the impact of globalization on the country's political system in Indonesia. The method used in the research uses qualitative methods with semiotic analysis techniques and data collection techniques, namely literature or literature studies. The results of the research show that globalization has created significant gaps in the political life of the country, the influence of political globalization on the state has many impacts, both on the positive side and on the negative side.